Initial empirical antibiotic therapy in kidney transplant recipients with pyelonephritis: A global survey of current practice and opinions across 19 countries on six continents - Coussement, Julien; Bansal, Shyam B; Scemla, Anne; Svensson, My H S; Barcan, Laura A; Smibert, Olivia C; Clemente, Wanessa T; Lopez-Medrano, Francisco; Hoffman, Tomer; Maggiore, Umberto; Catalano, Concetta; Hilbrands, Luuk; et al. (Transplant infectious disease, 2024)
BACKGROUND: Despite the burden of pyelonephritis after kidney transplantation, there is no consensus on initial empirical antibiotic management. METHODS: We surveyed clinicians throughout the world on their practice and opinions about the initial empirical therapy of post-transplant pyelonephritis, using clinical vignettes. A panel of experts from 19 countries on six continents designed this survey, and invited 2145 clinicians to participate. RESULTS: A total of 721 clinicians completed the survey (response rate: 34%). In the hypothetical case of a kidney transplant recipient admitted with pyelonephritis but not requiring intensive care, most respondents reported initiating either a 3rd-generation cephalosporin (37%) or piperacillin-tazobactam (21%) monotherapy. Several patient-level factors dictated the selection of broader-spectrum antibiotics, including having a recent urine culture showing growth of a resistant organism (85% for extended-spectrum ß-lactamase-producing organisms, 90% for carbapenemase-producing organisms, and 94% for Pseudomonas aeruginosa). Respondents attributed high importance to the appropriateness of empirical therapy, which 87% judged important to prevent mortality. Significant practice and opinion variations were observed between and within countries. CONCLUSION: High-quality studies are needed to guide the empirical management of post-transplant pyelonephritis. In particular, whether prior urine culture results should systematically be reviewed and considered remains to be determined. Studies are also needed to clarify the relationship between the appropriateness of initial empirical therapy and outcomes of post-transplant pyelonephritis.
Keywords: dospělí; lékařská praxe - způsoby provádění; kidney transplantation; průzkumy a dotazníky; Female; antimicrobial stewardship; beta-laktamasy; Adult; ženské pohlaví; Surveys and Questionnaires; lidé; Transplant Recipients; pyelonefritida; questionnaire; urinary tract infection; Anti-Bacterial Agents; cefalosporiny; transplantace ledvin; beta-Lactamases; Pyelonephritis; příjemce transplantátu; Kidney Transplantation; Male; Cephalosporins; Pseudomonas aeruginosa; lidé středního věku; kombinace léků piperacilin a tazobactam; mužské pohlaví; antibakteriální látky; Middle Aged; Practice Patterns, Physicians'; Piperacillin, Tazobactam Drug Combination; Humans